Genus eleutherine: a review of its distribution, traditional uses, phytochemistry, biological activities and their interchange names - Arbain, Dayar; Sriwahyuni, Klaudia; Darnis, Deny Susanti; Bakhtiar, M. Taher (Elsevier, 2022)
Eleutherine is a genus of bulbous, perennial and herbaceous plant in the Iridaceae family which have a wide range of biological activity. For instance, Eleutherine palmifolia (L.) Merr. (Dayak onion or bawang Dayak) is a plant that is widely used as an alternative medicine by people in Kalimantan. The name of Dayak onion is interchangeable between E. palmifolia (L.) Merr. with E. bulbosa (mill.) Urb. This systematic review was intended to explore a comprehensive information on distribution, traditional use, chemical content and in vivo and in vitro bioactivities of genus Eleutherine. The information was obtained through literature searches of published electronic data banks, such as Google Scholar, PubMed, PubChem, Elsevier, Science Direct, The Plant List, Global Biodiversity Information Facility (GBIF), JSTOR and Plant Science. ChemDraw software was used to draw bioactive molecules found in various species of the genus Eleutherine. Species of Eleutherine are distributed mostly in South America and Southeast Asia, and 2 species of them are found in Indonesia. Several chemical substances such as naphthoquinone, naphthalene, anthraquinone, polyketides and sterols have been found in the genus Eleutherine. Various bioactivities such as antifungal, antimicrobial, anti-inflam- matory, antidiabetic and anticancer genus Eleutherine were also found which were associated with several traditional uses. Several chemical constituents showed significant bioactivity related to anti-inflammatory activities. In this case, it is recommended to carry out further scientific research particularly in vivo and in vitro studies related to anti-inflammatory activities for developing phytopharmacy drugs in the future.